2020
DOI: 10.1186/s12903-020-01065-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between beverage consumption pattern and dental problems in Iranian adolescents: a cross sectional study

Abstract: Background: With regard to the increasing consumption rates of unhealthy beverages among adolescents, the main purpose of the present study was to determine the association between beverage intake pattern and dental caries and tooth erosion in this age group. Methods: A total sample of 600 adolescents was recruited in this study using a multistage cluster random sampling method in the city of Kerman, in the southeast of Iran, in 2017. Then, the Decayed, Missed and Filled Teeth (DMFT) index and the Tooth Wear I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 30 publications
3
31
0
Order By: Relevance
“…Consumption of different beverages and its frequency has a major role in preventing or accelerating dental caries. However, major arguments still exist in the literature [ 9 ]. This study aimed to evaluate the effect of beverage consumption on DMFT among Iranian adult population with the leading outcome that the tea and coffee beverages increased the DMFT, whereas other beverage groups had no substantial effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consumption of different beverages and its frequency has a major role in preventing or accelerating dental caries. However, major arguments still exist in the literature [ 9 ]. This study aimed to evaluate the effect of beverage consumption on DMFT among Iranian adult population with the leading outcome that the tea and coffee beverages increased the DMFT, whereas other beverage groups had no substantial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Also, consumption of different beverages and its frequency has a major role in preventing or accelerating dental caries. However, disparate opinions still exist to date [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no association between DMFT and the frequency of sugar consumption was found in our study, which was in agreement with results reported by Wening and co-workers for sighted children [ 45 ] due to multifactorial features of caries. A study on sighted adolescents in Iran showed sweetened soft beverages had been consumed by 25.6% of the participants with a significant effect on DMFT [ 26 ]. However, in our study, only one child reported daily use of soft drinks.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is a critical period in which adolescents socialize more and act more independently with respect to their health-related issues [ 21 ] With a common increase in BMI during adolescence [ 22 ], the consumption of junk food and drinks high in sugar increases during this period [ 23 ], especially soft drinks [ 24 , 25 ]. The pattern of beverage intake in Iranian adolescents is not favorable [ 26 ]. Oral health habits such as brushing and dental visits decrease from childhood to adolescence [ 27 ].…”
Section: Introductionmentioning
confidence: 99%